Фінансовий облік криптоактивів в Україні: сучасний стан, тенденції та перспективи - Гедз, М.Й.; Гуцалюк, О.М.; Остапенко, О.В.; Малишко, С.О. (Економічний вісник Донбасу, 2025)
Стаття присвячена аналізу сучасних підходів до фінансового обліку криптоактивів у міжнародній та вітчизняній практиці. Розглянуто класифікацію криптоактивів згідно з МСФЗ, зокрема МСБО 38 «Нематеріальні активи» та МСБО 2 «Запаси», а також виявлені суперечності між МСФЗ та US GAAP щодо їх оцінки та відображення у звітності. Проаналізовано дослідження 2022-2025 рр., які акцентують на необхідності створення окремого міжнародного стандарту, удосконалення методів оцінки та розкриття інформації. Наведено позиції науковців та аналітичних центрів (ACCA, PwC), що підкреслюють актуальність проблеми для глобального та українського облікового середовища. Визначено ключові тенденції розвитку методології та перспективи гармонізації облікових підходів. The article is devoted to a comprehensive analysis of modern scientific and practical approaches to the financial accounting of crypto-assets in both international and national contexts. It emphasizes that the absence of a unified international standard, high volatility, and the diversity of digital asset forms (bitcoins, tokens, NFTs) pose significant challenges for accountants, auditors, and regulators. The position of the IFRS Foundation is outlined, according to which crypto-assets mostly meet the definition of an intangible asset under IAS 38, and when held for sale, they are accounted for under IAS 2 «Inventories». Based on the analysis of 2022-2025 publications in leading academic journals and consulting company reports, it is established that current IFRS and US GAAP approaches differ substantially in the classification and measurement of crypto-assets, which limits the comparability of financial statements and complicates liquidity and cash flow analysis. Examples of studies are provided that justify the need to develop a separate «crypto-assets» category and apply fair value measurement with changes recognized in profit or loss, or to revalue them as intangible assets while minimizing the impact of volatility on profitability. The article also examines the accounting issues of stablecoins in the context of international standards. Special attention is paid to domestic research focusing on adapting the Ukrainian regulatory framework to European and international requirements. The conclusion is drawn that the global trend is aimed at creating a separate international standard for the accounting of crypto-assets, harmonizing valuation and disclosure methods, which is critically important for ensuring transparency and reliability of financial reporting.